Performance of Grazing Dromedary Camels (Camelus dromedarius) Supplemented with Concentrate Diet Based on Percentage Body Weight. - Ibrahim, H.; Suleiman, L.O.; Ahmed, S.A.; Ishiaku, Y.M.; Ibrahim, U.M.; Saidu, U.; Lawan, S.K.; Haliru, M.I.; Bawa, Z.A. (Nigerian Journal of Animal Science, 2026)
The study was conducted to determine the performance of dromedary camels supplemented with a concentrate diet based on their percentage body weight. Nine (9) dromedary camels with an average body weight of 420±3 kg was used for the experiment. The camels were selected, weighed and randomly assigned into three (3) dietary groups consisting of three (3) camels per group in a completely randomized design (CRD). The camels were allowed to graze and supplemented with a diet based on 1, 1.5 and 2% of their body weight and the experiment lasted for 90 days. Data collected on weight gain, hematology and serum biochemistry of the camels were subjected to analysis of variance (ANOVA) using SAS software package while significant differences among means were compared using the Duncan Multiple Range Test. Camels on 1 and 1.5% body weight supplements recorded a higher (P<0.05) weight gain (37.33 and 43.00 kg, respectively) compared to those supplemented with a diet based on 2% (21.50 kg) of their body weight. The average body weight gain was also higher (P<0.05) in camel supplemented with a diet based on 1 and 1.5% (0.41 and 0.48 kg/day, respectively) of their body weight followed by those on 2% (0.24 kg/day) body weight. However, camels supplemented with diet based on 1% body weight have a better (5.46) feed conversion ratio than those on 1.5 (7.41) and 2% (19.11) body weight. Furthermore, camels on a 1.5% body weight supplement recorded a higher (P<0.05) red blood cells than those supplemented with a diet based on 1 and 2% (4.13 ×1012/L) body weight. Similarly, camels on 1.5% body weight supplement recorded a higher (P<0.05) total protein (61.00 g/L), albumin (37.00 g/L) and globulin (24.00 g/L) concentration in the blood compared to those supplemented with 1 and 2% of their body weight. There were no significant differences in calcium, sodium, chlorine and potassium concentration in the blood. It was concluded that camels supplemented with a diet based on 1 and 1.5% body weight performed better than those on 2% body weight supplement. Hence, it is recommended that farmers should give supplementary feed based on 1 and 1.5% of their body weight to grazing camels for efficient feed utilization as well as better growth performance.